“Kind of Students… Kind of Staff” - Navigating Roles: A Thematic Exploration of PhD Demonstrators’ Experiences, Identity, and Career Implications - Dean Marshall, Nikki; Obretetskaya, Tatiana; Fox, Gemma; Cook, Caitlin; McAdams, Catrin; Parkin, Lee (Journal of University Teaching and Learning Practice, 2025)
We examined the experiences of 16 PhD demonstrators from Russell and non-Russell universities, exploring teaching benefits and challenges, dual student-teacher identities, and opinions on the “demonstrator” title. Through interviews and reflexive thematic analysis, four themes were found: 1) ambiguity in the demonstrator label persists despite the GTA alternative, reflecting a disconnect between title and role, 2) the unpredictability, heavy workload, and lack of freedom in the role contribute to stress and diminish enjoyment for demonstrators, 3) feelings of being unsupported due to inadequate preparation, lack of recognition, poor treatment by staff, and the burdens of casualised contracts, 4) positive aspects including the unique demonstrator-student relationship, skill development, mentorship, supportive community, and flexible scheduling that provides a break from PhD work. The study highlights the importance of recognizing the dual identity, finding a label that reflects their responsibilities, addressing stress factors, and enhancing support and recognition for individuals within these roles.